2021
DOI: 10.1155/2021/6641361
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Diseases and Disorders of Female Camels: An Assessment and Pathological and Bacteriological Study in Eastern Ethiopia

Abstract: Camels are the most efficient domesticated animals in arid and semiarid areas of the world. In Ethiopia, they are the main livestock kept to sustain the livelihoods of pastoralists, as camels are used for milk and meat production and also for transportation. However, she-camel reproductive diseases are one of the major constraints for camel-producing communities. A cross-sectional study was conducted from November 2018 to December 2019 to identify and characterize pathological lesions and isolate possible bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Of the total genital tracts examined, 36% (18/50) of organs had at least one gross pathological lesion of the reproductive systems. The organ-level pathological lesion of the genital tract was in line with the earlier reports of Getahun et al 52 in central Ethiopia that reported 34.2% and lower than Belina et al 54 who reported 64.6% pathological lesion in Eastern Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Of the total genital tracts examined, 36% (18/50) of organs had at least one gross pathological lesion of the reproductive systems. The organ-level pathological lesion of the genital tract was in line with the earlier reports of Getahun et al 52 in central Ethiopia that reported 34.2% and lower than Belina et al 54 who reported 64.6% pathological lesion in Eastern Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the anatomical classification in the present study, uterine abnormality 9 (18.0%), followed by cervicovaginal abnormality 6 (12.0%), and ovarian abnormality 3 (6.0%) were the most prevalent. The uterine abnormalities 9 (18.0%) found in this research were lower than Belina et al 54 in Eastern Ethiopia and who reported 41.2%. It was comparable to Getahun et al 52 in Addis Ababa, Adama, and Akaki abattoirs and Wajid 43 in Iraq, who reported 21.4% and 20%, respectively.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The reproductive disorders of the dromedary camel have not been studied as thoroughly as they are in the bovine. The prevalence of pathological disorders among reproductive organs had differences, where the highest proportion was observed in the uterus (Belina et al, 2021). Endometritis is one of the most common disorders, causing decreased fertility and high economic losses (Wernerry and Kumar, 1994).…”
Section: Introductionmentioning
confidence: 99%